The Influence of Distinctive Capabilities and Adaptive Capabilities on Business Model Adaptation and MSME Performance - adi wibowo, Wahyu; Anam, Khoirul (Journal Economic Business Innovation, 2024)
Purpose: This study examines the effect of distinctive capabilities and adaptive capabilities to business model adaptation and performance of Micro, Small and Medium Enterprises (MSMEs) in Indonesia.Method: The proposed hypotheses and the relationships between distinctive capabilities, adaptive capability, business model adaptation, and MSME performance were examined using Structural Equation Modeling (SEM) and regression analysis.Findings: The results show that both unique capabilities and adaptive capabilities play a crucial role in the adaptation of business models and the performance of MSMEs. The results prove that adaptive capability acts as a mediator between distinctive capabilities and business model adaptation, as well as between distinctive capabilities and MSME performance. Moreover, the relationship between distinctive capabilities on business model adaptation and MSME performance was moderated by adaptive capacity, indicating that firms with higher adaptive capacity are better placed to utilize their distinctive capabilities to achieve superior performance.Novelty: This paper adds to the dynamic capabilities literature by providing empirical insight into the relationships between distinctive capabilities, adaptive capability, business model adaptation and performance within MSMEs. This research sheds light on MSME success through a new lens of adaptive capacity as a mediator and moderator, providing an avenue for new ground in SME strategic management research particularly in emerging markets.Implications: The research indicates that MSMEs should strengthen their unique capabilities; also, the capabilities for market adaptability will be essential in this context for MSMEs to thrive and recover. Policymakers and practitioners must cultivate innovation, flexibility, and capability-building environments. Further exploration of the long-term impacts of these capabilities and extending the study to different geographical contexts or industries would provide a more in-depth understanding of their implications for business performance.